Sex differences in the association between chest computed tomography-defined sarcopenia and cardiovascular risk factors among inpatients - Chen, Xin; Zhu, Mingyu; Cao, Jie; Zuo, Didi; Chen, Zengai; Weng, Yurong; Jiang, Hua; Hu, Yaomin (Frontiers in Nutrition, 2024)
Background: Although sarcopenia has been proposed to be associated with increased risks of cardiovascular diseases (CVD), evidence exploring sex-related differences remains insufficient.We aimed to investigate sex differences in the prevalence of sarcopenia as defined by skeletal muscle area (SMA) in chest CT images and its association with CVD common risk factors.This cross-sectional study included 1340 inpatients from the Geriatric Department of Renji Hospital affiliated to Shanghai Jiaotong University School of Medicine. Age, sex, body mass index (BMI), smoking status, disease history, and clinical parameters were collected.Sarcopenia was determined by the chest CT images with a cut-off value of T12-SMA/height 2 < 25.75 cm 2 /m 2 in male and < 20.16 cm 2 /m 2 in female. Cardiovascular risk was determined using the Framingham risk score (FRS). The association between T12-SMA/height 2 defined sarcopenia and CVD risk factors by sex was evaluated by multivariate logistic regression.The prevalence of T12-SMA/height 2 defined sarcopenia (＜25.75cm 2 /m 2 for male, ＜20.16cm 2 /m 2 for female) was 54.03% overall, 48.09% for male and 63.19% for female. The proportion of male with high CVD risk was higher than that of female. The multivariate analysis model showed that T12-SMA/height 2 defined sarcopenia was independently associated with age (in male only), systolic blood pressure (SBP), cholesterol and high density lipoprotein cholesterol (HDL-C) of the 6 FRS cardiovascular risk indices.Our results indicated that T12SMA/height 2 -defined sarcopenia was more prevalent in male than female. Sarcopenia was associated with higher level of SBP and HDL-C, and lower level of cholesterol. Increasing age had a more significant effect on CVD risk in male.